Synovial lipoma of the ankle and foot: a rare case report - Wankhede, Aniket K.; Rathod, Rohit; Mote, Girish; C. M. Badole; Medhi, Mrigank (International Journal of Research in Orthopaedics, 2023)
Synovial lipomatosis is an extremely rare type of disease in which there is an excess of adipose tissue involving the synovium layer of joints or synovial sheath around the tendons causing pain, paraesthesia, and weakness. The most common site being reported till now is Knee joint or parapatellar space other joints such as elbows and shoulders are being reported after the knee joint, and the ankle joint is rarely reported 2 cases have been reported in the English literature. We report a case of a 28-year-old male presenting with swelling of the right foot for 12 years and developed symptoms of pain and tingling on the toes for 2-3 weeks. Multiple bony hard lesions were palpated on the base of the foot, ultrasonography (USG) showed a subcutaneous lesion around the extensor tendons of the foot and fine needle aspiration cytology (FNAC) had a picture of the synovial cyst. Surgical excision was done and histopathology was reported to be as a fibrofatty tissue with multiple adipocytes suggesting lipoma arborescent.